The sinus venosus progenitors separate and diversify from the first and second heart fields early in development. - Mommersteeg, M; Domínguez, J; Wiese, C; Norden, J; de Gier-de Vries, C; Burch, J; Kispert, A; Brown, N; Moorman, A; Christoffels, V (2010)
AIMS: During development, the heart tube grows by differentiation of Isl1(+)/Nkx2-5(+) progenitors to the arterial and venous pole and dorsal mesocardium. However, after the establishment of the heart tube, Tbx18(+) progenitors were proposed to form the Tbx18(+)/Nkx2-5(-) sinus venosus and proepicardium. To elucidate the relationship between these contributions, we investigated the origin of the Tbx18(+) sinus venosus progenitor population in the cardiogenic mesoderm and its spatial and temporal relation to the second heart field during murine heart development. METHODS AND RESULTS: Explant culture revealed that the Tbx18(+) cell population has the potential to form Nkx2-5(-) sinus venosus myocardium. Three-dimensional reconstruction of expression patterns showed that during heart tube elongation, the Tbx18(+) progenitors remained spatially and temporally separate from the Isl1(+) second heart field, only overlapping with the Isl1(+) domain at the right lateral side of the inflow tract, where the sinus node developed. Consistently, genetic lineage analysis revealed that the Tbx18(+) descendants formed the sinus venosus myocardium, but did not contribute to the pulmonary vein myocardium that developed in the Isl1(+) second heart field. By means of DiI labelling and expression analysis, the origin of the sinus venosus progenitor population was traced to the lateral rim of splanchnic mesoderm that down-regulated Nkx2-5 expression approximately 2 days before its differentiation into sinus venosus myocardium. CONCLUSION: Our data indicate that the cardiogenic mesoderm contains an additional progenitor subpopulation that contributes to the sinus venosus myocardium. After patterning of the cardiogenic mesoderm, this progenitor population remains spatially separated and genetically distinctive from the second heart field subpopulation.